2011
DOI: 10.1248/bpb.34.278
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Solid Supersaturatable Self-Emulsifying Drug Delivery System of Docetaxel with Improved Dissolution and Bioavailability

Abstract: Self-emulsifying drug delivery systems (SEDDS) are defined as isotropic mixtures of oils, surfactants, and co-solvents. The systems can form fine oil in water (o/w) emulsions (SEDDS) with a droplet size between 100 and 1000 nm or in microemulsions (SMEDDS) with a droplet size of less than 100 nm when meeting with aqueous media. SEDDS/ SMEDDSs may offer a new strategy for enhancing the oral bioavailability of poorly water soluble and lipophilic drugs. [1][2][3][4] However, recent studies suggest that there are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 31 publications
0
29
0
1
Order By: Relevance
“…However, the hygroscopic natures of such solidification excipients should be taken into consideration during formulation design because they may result in particle agglomeration. Chen et al reported that the solid su-SEDDS prepared by spray drying with lactose provides an effective approach for improving the dissolution and BA of docetaxel with a low level of emulsifying excipients and provides a reference for good stabilization and the safety of SEDDSs [113].…”
Section: Polysaccharide-based Carriersmentioning
confidence: 99%
“…However, the hygroscopic natures of such solidification excipients should be taken into consideration during formulation design because they may result in particle agglomeration. Chen et al reported that the solid su-SEDDS prepared by spray drying with lactose provides an effective approach for improving the dissolution and BA of docetaxel with a low level of emulsifying excipients and provides a reference for good stabilization and the safety of SEDDSs [113].…”
Section: Polysaccharide-based Carriersmentioning
confidence: 99%
“…Example: a) Recently, solid supersaturate SEDDS of docetaxel via spray drying technique have been prepared and it was found to have about 8.77-fold and 1.45-fold higher oral bioavailability as compared to free drug and conventional SEDDS [46]. b) Self-emulsifying drug delivery system was developed of tamoxifen which showed about 3.8-fold and 9-fold enhancement in oral bioavailability as compared to clinically used tamoxifen citrate and tamoxifen free base, respectively [14].…”
Section: Self Emulsifying Drug Delivery System (Sedds)mentioning
confidence: 99%
“…It has been generally found that the drug release is often retarded due to high lipophilic nature of the overall system, but considering the urge to increase the drug release rate; polymer lipid hybrid nanoparticles were developed. These are based on the same principle of SLNs, and incorporation of the ionic polymers helps in improving the encapsulation of water-soluble ionic drugs such as doxorubicin hydrochloride [46].…”
Section: Solid Lipid Nanoparticles (Slns)mentioning
confidence: 99%
“…in salicylic acid and docetaxel 8,44 SEDDS formulation, HPMC is used as precipitation inhibitor. A fivefold increase in bioavailability has been observed with PNU-91325 when HPMC in place of propylene glycol, is used as precipitation inhibitor 45 .…”
Section: Supersaturable Sedds (S-sedds) Tomentioning
confidence: 99%